2015
DOI: 10.1038/srep13628
|View full text |Cite
|
Sign up to set email alerts
|

Imaging transplanted stem cells in real time using an MRI dual-contrast method

Abstract: Stem cell therapies are currently being investigated for the repair of brain injuries. Although exogenous stem cell labelling with superparamagnetic iron oxide nanoparticles (SPIONs) prior to transplantation provides a means to noninvasively monitor stem cell transplantation by magnetic resonance imaging (MRI), monitoring cell death is still a challenge. Here, we investigate the feasibility of using an MRI dual-contrast technique to detect cell delivery, cell migration and cell death after stem cell transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…Alternative design strategies could help to overcome these limitations. For example, SPIO nanoparticles with gadolinium-based chelates (GdDTPA) allowed dual labelling of hMSCs, where live cells could be discriminated from dead cells in real time [75].…”
Section: Stem Cell Engineering With the Use Of Nanoparticlesmentioning
confidence: 99%
“…Alternative design strategies could help to overcome these limitations. For example, SPIO nanoparticles with gadolinium-based chelates (GdDTPA) allowed dual labelling of hMSCs, where live cells could be discriminated from dead cells in real time [75].…”
Section: Stem Cell Engineering With the Use Of Nanoparticlesmentioning
confidence: 99%
“…The authors suggested that this technique could be used to evaluate cell-based therapies, by providing timely feedback about cell distribution and when cell death occurs after transplantation. 64 One of the challenges in this field is to incorporate the SPIONs into the cells, as most stem cells are nonphagocytic. The incorporation of SPIONs by nonphagocytic cells can be facilitated by cationic compounds such as poly-l-lysine and protamine, due to their interaction with the negatively charged cell surface and subsequent endosomal uptake.…”
Section: Tracking Stem Cells With Superparamagnetic Iron Oxide Nanopamentioning
confidence: 99%
“…Among the several imaging techniques including CT, PET, SPECT, MRI, optical imaging, and ultrasound, MRI can provide high spatial and temporal resolution with the use of iron oxide-particles and 19 F-based probes for image-guided immune cell delivery and visualization of immune cell homing and engraftment, inflammation, cell physiology and gene expression (48). Available MRI techniques include using Gadoliniumbased T1 contrast agent, superparamagnetic iron oxide nanoparticles (SPIONs) based T2 contrast agent, and molecular probes containing 19 with SPIONs has been used in cell-based therapy (49,50). It has been explored previously to image immune cell (such as CD4 T+ cells, CD8 T+ cells, and Mac1+ cells) location and homing in the central nervous system of mice with superparamagnetic antibodies (51).…”
Section: Discussionmentioning
confidence: 99%